Behaviour of Concrete by Partial Replacement of Coarse Aggregate with Recycled Plastic Granules (International Journal of Innovative Research in Computer Science & Technology, 2022)
In this paper All countries are focusing  on sustainable technology that can be economical and adopted for the use of concrete in a better way. Concrete  is most widely used construction material and it possess very low tensile strength, shear strength and brittle  characteristics. In order to improve this property a new construction materials were developed through research and development work called asbestos fiber concrete and  recron 3s fibers concrete. M30 gradeof concrete was designed. The addition of asbestos fiber and recron 3S  fiberthe concrete. To determine the properties like tensile strength, compressive strength and flexural strength were  performed at different ages like 7,14 and 28 days. The  addition of asbestos fiber varies from 0%, 0.25%, 0.5%,  0.75%and 1% by volume of concrete and recron 3S fiber  varies from 0%, 0.25%, 0.5%, 0.75% and 1% by volume of concrete.
Keywords: Asbestos fiber concrete; Recron 3s fiberconcrete; Tensile strength and compressive strength